Displacing democracy: economic segregation in America - Widestrom, Amy (American governance., 2015)
Displacing Democracy demonstrates how neighborhoods segregated along economic lines create conditions encouraging high levels of political activity, including civic and political mobilization and voting, among wealthier citizens while simultaneously discouraging and impeding the poor from similar forms of civic engagement.